International influences on United Kingdom crime control and penal policy in the 1990s - Newburn, Tim (UK Data Service, 2020)
The aim of the study was to describe and analyse the extent and nature of United States influence on United Kingdom criminal justice policy during the 1990s. More specifically, the researchers set out to: develop detailed case histories of policy change in the key areas associated with the UK learning from US developments (such as privatized corrections, zero tolerance policing, and 'two' and 'three strikes' sentencing); assess critically the extent to which these developments were actually informed and shaped by US influences; analyse the key processes of policy transfer between the US and UK, and to describe and analyse the development of transnational policy networks in criminal justice. The first stage of the research involved a detailed collation and review of documentary sources in each of the key areas of policy change -- government publications, parliamentary and congressional debates and reports, newspaper archives, pressure group and think tank publications, and academic books and journals. Following this initial mapping of case histories of policy change, around 100 semi-structured interviews were conducted with key players in the policy process, both in the UK and in the USA, including politicians, policy makers, journalists, representatives of pressure groups and NGOs, academics and criminal justice professionals.